Copyrolysis energy analysis of municipal solid waste and agricultural stalk. Issue 2 (20th August 2015) - Jia, Jinwei; Lu, Mingyuan; Liu, Lu; Yang, Fengsheng; Fu, Xiaoheng; Fu, Xingmin; Yang, Di; Shu, Xinqian
Abstract : Co‐pyrolysis of municipal solid waste with cassava stalk or corn stalk was investigated in this work. Profiles of the product yields versus different agricultural stalk adding ratios during pyrolysis at 600°C reveal that the char yields reduced, and the liquid and gas yields increased at start‐up stage but afterwards decreased with adding ratios of agricultural stalk increasing. The differences between experimental and theoretical yields of char ranged from 18.26 to 10.35% as cassava stalk ratios from 10 to 50%, and from 8.13 to 11.09% as corn stalk ratios from 10 to 50%. The statistical analysis of theoretical and experimental data implied the synergistic effect between municipal solid waste and agricultural stalk during co‐pyrolysis process. The energy balance showed that pyrolysis of municipal solid waste alone could not produce enough pyrolysis liquid to compensate the energy consumption of pyrolysis system, and the co‐pyrolysis system could dispose of municipal solid waste without extra energy input. The calculated results also showed that the feed stock comprised of 49.21% of cassava stalk or 40.12% of corn stalk could guarantee the energy balance of the co‐pyrolysis system. © 2015 American Institute of Chemical Engineers Environ Prog, 35: 547–552, 2016